2018
DOI: 10.1038/s41467-018-05814-0
|View full text |Cite
|
Sign up to set email alerts
|

Precession-band variance missing from East Asian monsoon runoff

Abstract: Speleothem CaCO3 δ18O is a commonly employed paleomonsoon proxy. However, inferring local rainfall amount from speleothem δ18O can be complicated due to changing source water δ18O, temperature effects, and rainout over the moisture transport path. These complications are addressed using δ18O of planktonic foraminiferal CaCO3, offshore from the Yangtze River Valley (YRV). The advantage is that the effects of global seawater δ18O and local temperature changes can be quantitatively removed, yielding a record of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
132
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(149 citation statements)
references
References 91 publications
6
132
2
Order By: Relevance
“…An estimated ∼ 80 % of the mean annual discharge of the river Changjiang is supplied to the ECS (Ichikawa and Beardsley, 2002) and in situ observational data show a pronounced negative correlation between the Changjiang discharge and SSS in July (Delcroix and Murtugudde, 2002). Consistently, previous studies from the OT reported such a close relationship between summer EAM and SSS back to the late Pleistocene (Chang et al, 2009;Clemens et al, 2018;Kubota et al, 2010;Sun et al, 2005).…”
Section: Oceanographic Settingsupporting
confidence: 77%
“…An estimated ∼ 80 % of the mean annual discharge of the river Changjiang is supplied to the ECS (Ichikawa and Beardsley, 2002) and in situ observational data show a pronounced negative correlation between the Changjiang discharge and SSS in July (Delcroix and Murtugudde, 2002). Consistently, previous studies from the OT reported such a close relationship between summer EAM and SSS back to the late Pleistocene (Chang et al, 2009;Clemens et al, 2018;Kubota et al, 2010;Sun et al, 2005).…”
Section: Oceanographic Settingsupporting
confidence: 77%
“…To quantify the contribution of convection to 18 O P , we can employ a similar tagging technique to tag condensation and evaporation processes in convection schemes in the future. Furthermore, karst system processes can distort 18 (Clemens et al, 2018, Site U1429 of the International Ocean Discovery Program) representing the monsoon runoff showed that it did not feature the 23-kyr cycles present in speleothem records. Although this discrepancy can be explained by the possibility that the 18 O signal in this marine sediment is also influenced by shoreline migration due to sea level changes, and speleothem 18 O represents large-scale circulation variations as stated in this paper rather than local rainfall amount, this finding still should make us rethink why speleothem 18 O primarily responds to insolation in the precessional band.…”
Section: Discussionmentioning
confidence: 99%
“…This is a regional phenomenon as a similar trend is found in the middle Okinawa Trough (Chen et al 2010) and western Pacific warm pool (Stott et al 2002) based on Mg/Ca-based SST from G. ruber. However, alkenone-based SST, which is interpreted as reflecting an annual mean SST, shows the lowest values during LGM in the northern ECS (Ijiri et al 2005;Clemens et al 2018). The proxy-dependent results suggest seasonality in the SST evolution since the last glacial period.…”
Section: Changes In Sst Local Seawater δ 18 O and Sssmentioning
confidence: 82%
“…The age model was further fine-tuned to a composite record of the Chinese δ 18 O sp (Additional file 3: Figure S3 and Additional file 4: Table S1), assuming an in-phase relationship between the climate in the northern ECS and hydroclimate variability over China as mentioned in Clemens et al (2018). This assumption is justified in the following discussion by correlating the AT tephra layer in our core and its age with others.…”
Section: Age Modelmentioning
confidence: 99%